The Remission Rate of Type 2 Diabetes Outpatients with Premixed Insulin: The Result of a 5-Year Prospective Study - Liu, Fu-peng; Sun, Ming-hui; Zhao, Jun-yu; Yang, Ming; Zhou, Xiao-jun; Zhang, Zhong-wen; Dong, Jian-jun; Liao, Lin (Hormone and Metabolic Research, 2020)
The aim of the study was to evaluate the remission rate with short-term premixed insulin therapy in newly diagnosed type 2 diabetes outpatients and investigate predictors contributing to the remission rate. A 5-year prospective study was conducted with a total of 170 patients enrolled. Patients were treated with premixed insulin monotherapy or insulin in combination with one or two oral drugs. After glucose levels were well controlled, insulin and oral drugs were discontinued in a stepwise manner. The prolonged and partial remission rates were calculated and the possible factors contributing to remission were also analyzed. A total of 164 subjects completed the research study. The prolonged remission, partial remission and non-remission rates at the 5-year follow-up were 9.8, 59.8, and 30.5%, respectively. The remission rate was negatively correlated with disease duration (r=0.39). The combined rate of remission (prolonged and partial remission) significantly decreased when the duration was longer than 16 days, and reduced to approximately 50% after 1 month. Moreover, 75% of prolonged remission patients had duration of < 16 days. At the 5-year follow-up, the prolonged remission rate was 9.8% and the partial remission rate was 59.8%. Furthermore, the duration after diagnosis is an independent predictor of remission rate, and initiation of short-term premixed insulin therapy within the first 16 days of diabetes diagnosis is very important for remission. This is the first study to evaluate the remission rate associated with short-term premixed insulin therapy in recently diagnosed type 2 diabetes outpatients. At the 5-year follow-up, the prolonged remission rate was 9.8% and the partial remission rate was 59.8%. The duration of diabetes was identified as an independent predictor of drug-free remission. The initiation of short-term premixed insulin therapy within 15 days of diabetes onset is particular importance for remission.
Keywords: type 2 diabetes; outpatients; short-term premixed insulin therapy; remission rates; prospective study